(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Assessment is an inseparable part of teaching, influencing the decisions teachers make, the actions they take and the suggestions they offer for student learning. Classroom assessment, specifically, refers to methods and procedures used by the language teacher for gathering, analyzing, interpreting and using information about student’s language abilities for decision making purposes. Recently, educators and scientists have been becoming more interested in the requirements of assessment procedures in the scope of foreign language teaching and the learning process, as forms of assessment have been changing. The assessment procedures relate to authenticity, practicality, reliability, validity and wash back, and are considered the basic principles of assessment in foreign language teaching and learning. The main value of these principles is to distinguish the effects of assessment and review any classroom based issues between the teacher and the student. As the assessment process affects both teachers and students, significance and consideration should be given to assessment procedures in foreign language teaching.